Is there a role for immune checkpoint blockade with ipilimumab in prostate cancer?. (24th February 2013) - Cha, Edward; Small, Eric J.
Abstract: Treatment for advanced prostate cancer has and will continue to grow increasingly complex, owing to the introduction of multiple new therapeutic approaches with the potential to substantially improve outcomes for this disease. Agents that modulate the patient's immune system to fight prostate cancer – immunotherapeutics – are among the most exciting of these new approaches. The addition of antigen‐specific immunotherapy to the treatment of castration‐resistant prostate cancer (CRPC) has paved the way for additional research that seeks to augment the activity of the immune system itself. The monoclonal antibody ipilimumab, approved in over 40 countries to treat advanced melanoma and currently under phase 2 and 3 investigation in prostate cancer, is thought to act by augmenting immune responses to tumors through blockade of cytotoxic T‐lymphocyte antigen 4, an inhibitory immune checkpoint molecule. Ipilimumab has been studied in seven phase 1 and 2 clinical trials that evaluated various doses, schedules, and combinations across the spectrum of patients with advanced prostate cancer. The CRPC studies of ipilimumab to date suggest that the agent is active in prostate cancer as monotherapy or in combination with radiotherapy, docetaxel, or other immunotherapeutics, and that the adverse event profile is as expected given the safety data in advanced melanoma. The ongoing phase 3 program will further characterize the risk/benefit profile of ipilimumab in chemotherapy‐naïve and ‐pretreated CRPC. Abstract : Ipilimumab, a cytotoxic T‐lymphocyte antigen 4 (CTLA‐4)‐blocking monoclonal antibody, is thought to augment natural immune responses to tumors. Ipilimumab is approved in several countries to treat advanced melanoma, and it is now under phase 3 investigation in prostate cancer based on the results of 7 smaller clinical trials, as reviewed in this article.